Illicit enrichment A guide to laws targeting unexplained wealth - Dornbierer, Andrew (Basel Institute on Governance, 2021)
Illicit Enrichment by Andrew Dornbierer provides a comprehensive guide to illicit enrichment laws and their application to target unexplained wealth and recover proceeds of corruption and other crimes. The book covers both criminal and civil-based laws from around the world. Investigators, prosecutors, legislators and academics alike will benefit from the clear descriptions and practical guidance on different approaches to targeting unexplainable increases in wealth, how to establish cases in court, and common legal challenges to illicit enrichment laws.Features:•Extensive analysis of jurisprudence and cases around the world•Tables, flow charts and graphics explaining key concepts•Discussion of common questions and challenges•A collection of laws from 103 jurisdictions, also as an online database•A step-by-step guide to financial investigation and source and application analysis to support illicit enrichment casesIllicit Enrichment was developed and published by the Basel Institute on Governance through its International Centre for Asset Recovery, with research support from the NYU School of Law.See: illicitenrichment.baselgovernance.org